SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK PENENTUAN PRESTASI KINERJA DOKTER PADA RSUD. SUKOHARJO - , TOMINANTO ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The doctor is the main resource in the health service, therefore it is necessary that professional and qualified doctors to improve the quality of healthcare. One effort to boost the performance of physicians is to do a performance evaluation. Physician performance evaluation system conducted in RSUD. Sukoharjo is still based solely on DP3 element so that the assessment is still very subjective. Based on these problems, hence in this study developed a decision support system using the method of Analytical Hierarchy Process (AHP) for the determination of physician performance achievement. These system uses criteria and intensity specified by the user, are processed by AHP calculations, and generate a list of physician performance assessment of the achievement. The result of this decision support system testing has been concluded that the system has been running correctly, so the system can be used as the basis for leaders in taking a more objective decision.